2016
DOI: 10.1088/0953-8984/28/49/495703
|View full text |Cite
|
Sign up to set email alerts
|

Zero energy modes in a superconductor with ferromagnetic adatom chains and quantum phase transitions

Abstract: We study Majorana zero energy modes (MZEM) that occur in an s-wave superconducting surface, at the ends of a ferromagnetic (FM) chain of adatoms, in the presence of Rashba spin-orbit interaction (SOI) considering both non self-consistent and self-consistent superconducting order. We find that in the self-consistent solution, the average superconducting gap function over the adatom sites has a discontinuous drop with increasing exchange interaction at the same critical value where the topological phase transiti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 80 publications
0
7
0
Order By: Relevance
“…The adatoms act as magnetic impurities for the host superconductor and give rise to Yu-Shiba-Rushinov (YSR) states which hybridize to form a band dispersing within the energy gap of the superconductor [17][18][19][20]. In suitable parameter regimes, SOC induces chiral TSC in the YSR impurity band [16,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]]. An adatom chain, therefore, mimics the physics of the onedimensional Kitaev model [36] which contains isolated MBS at the ends of the chain.…”
mentioning
confidence: 99%
“…The adatoms act as magnetic impurities for the host superconductor and give rise to Yu-Shiba-Rushinov (YSR) states which hybridize to form a band dispersing within the energy gap of the superconductor [17][18][19][20]. In suitable parameter regimes, SOC induces chiral TSC in the YSR impurity band [16,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]]. An adatom chain, therefore, mimics the physics of the onedimensional Kitaev model [36] which contains isolated MBS at the ends of the chain.…”
mentioning
confidence: 99%
“…Superconductorferromagnet heterostructures do not require the application of an external magnetic field and, therefore, are advantageous with respect to other platforms. Following this line of argument, topological superconductivity and MZMs have been demonstrated to emerge in half-metal/superconductor [14] or ferromagnet/unconventional superconductor [15] heterostructures, in ferromagnetic wires proximised to conventional superconductors [16][17][18] and in ferromagnetically aligned chains of magnetic impurities embedded in conventional superconductors [19][20][21][22][23][24][25][26]. Spin-orbit coupling is an essential component in all of these proposals.…”
Section: Majorana Zero Modes In Superconductor/ferromagnet Heterostructuresmentioning
confidence: 99%
“…Based on Hamiltonian Equation ( 24) describing the FM wire, we derive, in this section, the criteria regarding the exchange field h FM and the chemical potential µ FM for which MZMs emerge localised at the edges of the FM. To this aim, we consider periodic boundary conditions and transform Hamiltonian Equation (24) in momenta k space. Introducing the spin-dependent Nambu spinor…”
Section: Topological Criteria For the Ferromagnetic Wirementioning
confidence: 99%
“…If the number of magnetic impurities is large enough there are bound states inside the gap that have zero energy and constitute self-conjugate Majorana fermions. It has been shown that the quantum phase transition that results from the closing of the gap as a function of the coupling between the local impurities and the conduction electron spin density coincides with the topological transition to a topological phase with the Majorana fermions [51].…”
Section: Effects Of Disorder In Z Class Superconductorsmentioning
confidence: 99%